Sub-volume averaging of repetitive structural features in angularly filtered electron tomographic reconstructions - Kováčik, Lubomír; Kereïche, S; Matula, Pavel; Raška, Ivan (Folia biologica (Praha), 2014)
Electron tomographic reconstructions suffer from a number of artefacts arising from effects accompanying the processes of acquisition of a set of tilted projections of the specimen in a transmission electron microscope and from its subsequent computational handling. The most pronounced artefacts usually come from imprecise projection alignment, distortion of specimens during tomogram acquisition and from the presence of a region of missing data in the Fourier space, the "missing wedge". The ray artefacts caused by the presence of the missing wedge can be attenuated by the angular image filter, which attenuates the transition between the data and the missing wedge regions. In this work, we present an analysis of the influence of angular filtering on the resolution of averaged repetitive structural motives extracted from three-dimensional reconstructions of tomograms acquired in the single-axis tilting geometry.
Keywords: Chlamydomonas reinhardtii; Microtubules; Kinesins; Electron Microscope Tomography; tomografie elektronová; počítačové zpracování obrazu; mikrotubuly; axonema; kineziny; Image Processing, Computer-Assisted; Axoneme